The influence of the scientific approach learning model on the learning outcomes of Buddhism and students' creative thinking skills - Ni Putu Sukmaliani; Tjhia Khie Khiong; Endang Sri Rejeki (SMARATUNGGA: JURNAL OF EDUCATION AND BUDDHIST STUDIES, 2021)
The study aims to analyze the effect of the learning model with a scientific approach on the learning outcomes of Buddhism and students' creative thinking skills. The study Employing quantitative research, this study carries out a pre-experimental design with one group pretest-posttest design. The research population is SMP Negeri Uggulan Doremi students, and the samples are the grade VIIA students in the 2020/2021 academic year. The instruments used are science learning outcomes tests and creative thinking skills tests. Descriptive statistics and T-test analyze data on learning outcomes and creative thinking skills. The results show that there is a significant difference in (1) learning outcomes between students who were taught using the direct instruction model and students who were taught using the scientific approach (p<0.05), and (2) students' creative thinking skills between students who were taught using the direct instruction model and students who are taught using the scientific approach (p<0.05). This study proves that the scientific approach is an effective learning model to improve student learning outcomes and creative thinking skills.